Spare - Harry, Prince, Duke of Sussex, 1984- (New York, NY : Random House Large Print, 2023)
Prince Harry$1 (Bs (Duke of Sussex) memoir$1 (Bin which he discusses the effect of his mother Princess Diana$1 (Bs death on his life$1 (Bis full of insight, revelation, self-examination and hard-won wisdom about the eternal power of love over grief.s
Keywords: Harry, -- Prince, Duke of Sussex, -- 1984-; Meghan, -- Duchess of Sussex, -- 1981-; Princes -- Great Britain -- Biography; Windsor, House of -- Biography; Memoirs; Personal narratives; Autobiographies; Large type books